HUBUNGAN TINGKAT PENGETAHUAN IBU DAN KETERSEDIAAN FASILITAS PENUNJANG ASI EKSKLUSIF DENGAN PEMBERIAN ASI DI WILAYAH KERJA PUSKESMAS BONOROWO KABUPATEN KEBUMEN - Nurdiana, Ika (2016)
The successfully of giving breast milk exclusive can be supported by mother's knowledge about that concern of the benefits and losses if they don't giving breast milk exclusive. A good knowledge followed by will would be push the mothers to give breast milk exclusive to their babies. The availability of a good support facilities about breast milk exclusive. In the fact, breast milk support facilities are still few and small. The aim of this study is to know the relationship of mother's knowledge and the availability of the breast milk support facilities exclusive with giving breast milk. The methods of this research is quantitative research with analytic survey. The design of this research used the cross sectional. The population is mothers with babies between 7 until 12 months with 242 respondents. Samples that used 60 respondents with inclusion criteria. Consist of 30 mothers that giving breast milk exclusive and 30 mothers without it, to their babies. The sampling technique used accidental sampling. Data collected by questionnaires. The analyse that used chi square test with 5% error rate (p=0.05), the result of the cross sectional between mother's knowledge with giving breast milk is p value=0.036. Because p value <0.05 it means there are the relationship of mother's knowledge with giving breast milk in the working area of Bonorowo Health Centers. The result of cross sectional between the availability of breast milk support facilities exclusive with giving breast milk is p value=0.009, because p value <0.05, it means there are the relationship of breast milk support facilities exclusive with giving breast milk in the working area of Bonorowo Health Centers. The suggestion for the next study is used the other sampling technique, causes by uneffective accidental sampling.